Partitioning of assimilates in cotton and boll development - de Souza, José Gomes; da Silva, Jorge Vieira (Pesquisa Agropecuaria Brasileira, 1992)
By randomly crossbreeding of several selected cotton cultivars (Gossypium hirsutum L. r. latifolium Hutch), two populations were established and designated G-1 and G-2. G-1 gave a higher ginning percentage, lower seed weight, and shorter lint than G-2. Width of fully expanded cotyledons and soluble protein content was higher in G-2 than in G-1. The soluble protein content in seeds of cotton bolls increases till the 10th day after flowering and decreases afterwards. In carpels the soluble protein content decreases constantly with increase of age. Soluble sugars in stems, leaves and carpels from the first cotton bolls follow the same pattern. The starch in stems, leaves and carpels content followed the same pattern, increasing from 5th to 10th day and decreasing afterwards, except in G-2 that continues to increase in the carpels. Starch content in seeds increased in both cultivars with time while the soluble sugars decreases.